Well documented - Konango, Gilbert (Technical Centre for Agricultural and Rural Cooperation, 2006)
Engonga Prétextat: I lost my job as assistant accountant in 1988. It s thanks to Spore that I had the idea of turning to farming. Since then, I ve read every issue